Anti-double Stranded DNA Antibodies: Origin, Pathogenicity, and Targeted Therapies - Wang, Xiaoyu; Xia, Yumin (Frontiers in Immunology, 2019)
Systemic lupus erythematosus (SLE) is characterized by high-titer serological autoantibodies, including antibodies that bind to double-stranded DNA (dsDNA). The origin, specificity, and pathogenicity of anti-dsDNA antibodies have been studied from a wider perspective. These autoantibodies have been suggested to contribute to multiple end-organ injuries, especially to lupus nephritis, in patients with SLE. Moreover, serum levels of anti-DNA antibodies fluctuate with disease activity in patients with SLE. By directly binding to self-antigens or indirectly forming immune complexes, anti-dsDNA antibodies can accumulate in the glomerular and tubular basement membrane. These autoantibodies can also trigger the complement cascade, penetrate into living cells, modulate gene expression, and even induce profibrotic phenotypes of renal cells. In addition, the expression of suppressor of cytokine signaling 1 is reduced by anti-DNA antibodies simultaneously with upregulation of profibrotic genes. Anti-dsDNA antibodies may even participate in the pathogenesis of SLE by catalyzing hydrolysis of certain DNA molecules or peptides in cells. Recently, anti-dsDNA antibodies have been explored in greater depth as a therapeutic target in the management of SLE. A substantial amount of data indicates that blockade of pathogenic anti-dsDNA antibodies can prevent or even reverse organ damage in murine models of SLE. This review focuses on the recent research advances regarding the origin, specificity, classification, and pathogenicity of anti-dsDNA antibodies and highlights the emerging therapies associated with them.